Konsep At-Tawazun Terhadap Independent Woment Di Era Generasi Z Menurut Yusuf Al Qardhawi - Abdullah Sani Kurniadinata; Maya Viada (Peduli Riset dan Pengabdian Masyarakat, 2025)
he phenomenon of independent women is growing stronger among Generation Z along with the development of globalization and digitalization. Women of this generation demonstrate independence in the educational, economic, and social fields, but often face a dilemma between individual freedom and religious values. This study uses a qualitative method with a library research approach, namely by examining the works of Yusuf al-Qardhawi such as Fiqh al-Mar'ah al-Muslimah, al-Wasathiyyah al-Islamiyyah, and al-Sahwah al-Islamiyyah, as well as other supporting literature. The analysis was conducted to understand how the concept of balance in his thinking can be applied to the social reality of Generation Z which emphasizes women's independence. The results of the study show that Yusuf al-Qardhawi views At-Tawazun as a universal principle in Islam that regulates the balance between rights and obligations, this world and the hereafter, reason and revelation, and between men and women. In the context of independent women, al-Qardhawi emphasized that Islam provides space for women to be independent and play an active role in society as long as they maintain moral values, family responsibilities, and their feminine nature. According to him, women's independence must be oriented towards the benefit and purpose of life in accordance with the maqashid al-shari'ah, not on unlimited freedom as promoted by Western feminism. Thus, through the concept of At-Tawazun, Yusuf al-Qardhawi offers a paradigm of balance that is relevant for modern Muslim women to achieve independence that is harmonious, ethical, and in line with Islamic teachings.